Identifikasi Potensi Turbelensi di Wilayah Penerbangan Indonesia Berdasarkan Analisis Richardson Number (Ri) Menggunakan Data ECMWF ERA5 (Studi Kasus Tahun 2022) - Riswanto, Rafli Muhammad Haris; Mustofa, Musa Ali; Saragih, Immanuel Jhonson Arizona (Buletin GAW Bariri (BGB), 2024)
Turbulence is an atmospheric phenomenom that that significanly impacts aviation safety, particularly in Indonesia, which features complex tropical weather conditions and dense air traffic. The identification and mapping of turbulence potential are crucial for improving aviation safety and operational efficiency. This study aims to map the turbulence potential in Indonesian flight regions using the Richardson Number (Ri) for the year 2022. The data utilized in this research are sourced from the European Centre for Medium - Range Weather Forecasts (ECMWF) Reanalysis Version 5 (ERA5) and radiosonde observation. ERA5 data were employed to calculated Ri, which can detect turbulence potential based on meteorological parameters such as wind speed and temperature. Ri calculations were aggregated monthly and annually for temporal and spatial analysis. Validation was conducted using radiosone data to verify turbulence events and meteorological parameters across various atmospheric levels. Spatial observations across Indonesia revealed significant turbulence events on January 18, July 2, and December 26, 2022, with notable daily fluctuations. Geographically, regions along the sothern coasts of Java and Sumatera, as well as certain areas in Kalimantan and Papua, exhibited higher frequencies of turbulence. These patterns are influenced by seasonal weather condition and complex local geopraphical features. Data validation demonstrated good agreement between ERA5 data and radiosonde measurements for temperature parameters, although significant differences were found in the zonal and meridional wind components. This indicates that the reialbility of the generated turbulence potential maps could be enhanced by integratting local data and further refining validation methods for wind components. These findings highlight the importance of ultilizing accurate local data to effectively predict and mitigate the impacts of turbulence on aviation in Indonesia